(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2011)
The aim of the research is to examine the context of the Willemsplein development. Willemsplein was a public urban-square in Dutch c¬o¬lonial era (plein) at Jembatan Merah area. Willemsplein, which in the following time became Surabaya urban heritage, changes into a private me¬¬mo¬rial park which is known as Taman Jayeng¬rono (Jayengrono Park). The context of this park is the most important aspect in the urban-square de¬¬velopment be¬cause the attainment of the suitability and continuity of the visual-formal, memory, and meaning of the urban-square arrangement implicitely shows certain character. The research method is a qualitative des¬crip¬tive method which is implied to analyze the comparation of the arrangement of Jayengrono Park in the past and at present in three phases. The first phase is the identification of the chronological formation of Jayengrono Park by using the analysis technique of the historical period suitability (diachronic reading) towards the phy¬sical arrangement (synchronic reading). The second phase is the identification of the proportion of Jayengrono Park by using the analysis technique of the measurement of the square-proportion ratio. The last phase is the iden¬tification of the place by using the analysis technique of simulation. The research shows that the Willems¬ple¬in arrangement combines the classical European open-square arrangement of the two development centers in Italy and France through the usage of the sequences of streets, rivers and bridges and the usage of the street axes as the mathematical result of the square proportion. The deletion of the intagible identitiy in Willemsplein shows that the character context cannot be attained; or it can be interpreted as the loss of the identity of the cu¬l¬tural reservation in the development of Jayengrono Park. Concurrently, it means that the development of Ja¬yeng¬rono Park is merely as an urban green open-square.